2019
DOI: 10.1186/s40164-019-0132-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-organ failure induced by Nivolumab in the context of allo-stem cell transplantation

Abstract: Background Immune checkpoint inhibitors have radically changed the landscape of anti-tumor therapies in several malignancies. However the adverse events associated with immune checkpoint blockade in combination with other treatments remains to be thoroughly documented. Here we report the case of a 33-year-old male with classical Hodgkin lymphoma who was successfully treated for lymphoma but experienced serious and eventually fatal multisystem organ failure following nivolumab administration and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…cTnI, cardiac troponin I; cTnT, cardiac troponin T; BNP, brain natriuretic peptide; TTE, transthoracic echocardiogram; ECG, electrocardiogram; CMR, cardiovascular magnetic resonance; CK-MB, creatine kinase-myocardial band; NT-pro BNP, N-terminal pro-brain natriuretic peptide; CPK, creatine phosphokinase; CK, creatine kinase; CRP, C-reactive protein; AChR Ab, acetylcholine receptor antibody; EF, ejection fraction; LV, left ventricular; LVEF, left ventricular ejection fraction; PE, pericardial effusion; MR, mitral regurgitation; AR, aortic regurgitation; BVD, bi-ventricular dilatation; BAD, bi-atrial dilatation; LVD, left ventricle dilatation; RVD, right ventricle dilatation; TR, tricuspid regurgitation; LAFB, left anterior fascicular block; LBBB, left bundle branch block; RBBB, right bundle branch block; LVH, left ventricular hypertrophy; RAE, right atrial enlargement; LAE, left atrial enlargement; GBF, global biventricular failure; LGE, late gadolinium enhancement; EGE, early gadolinium enhancement AF, atrial fibrillation; PAP, pulmonary artery pressure; LVSF, left ventricular systolic function; RVSF, right ventricular systolic function; RHF, right heart failure; CHB, complete heart block; MI, myocardial infarction; MAB, multiple apical thrombi; CAB, complete atrioventricular block(a* = 9 (Norwood et al, 2017; Ganatra and Neilan, 2018; Katsume et al, 2018; Monge et al, 2018; Thibault et al, 2018; Agrawal et al, 2019; Charles et al, 2019; Sakai et al, 2019; Sharma et al, 2019). (b* = 7) (Ederhy et al, 2018; Frigeri et al, 2018; Matson et al, 2018; Agrawal et al, 2019; Charles et al, 2019; Fazel and Jedlowski, 2019; Khoury et al, 2019). (c* = 8) (Johnson et al, 2016a; Arangalage et al, 2017; Chen et al, 2018; Martin Huertas et al, 2019; Salem et al, 2019).…”
Section: The Diagnosis Of Immune Checkpoint Inhibitor-associated Cardmentioning
confidence: 99%
See 2 more Smart Citations
“…cTnI, cardiac troponin I; cTnT, cardiac troponin T; BNP, brain natriuretic peptide; TTE, transthoracic echocardiogram; ECG, electrocardiogram; CMR, cardiovascular magnetic resonance; CK-MB, creatine kinase-myocardial band; NT-pro BNP, N-terminal pro-brain natriuretic peptide; CPK, creatine phosphokinase; CK, creatine kinase; CRP, C-reactive protein; AChR Ab, acetylcholine receptor antibody; EF, ejection fraction; LV, left ventricular; LVEF, left ventricular ejection fraction; PE, pericardial effusion; MR, mitral regurgitation; AR, aortic regurgitation; BVD, bi-ventricular dilatation; BAD, bi-atrial dilatation; LVD, left ventricle dilatation; RVD, right ventricle dilatation; TR, tricuspid regurgitation; LAFB, left anterior fascicular block; LBBB, left bundle branch block; RBBB, right bundle branch block; LVH, left ventricular hypertrophy; RAE, right atrial enlargement; LAE, left atrial enlargement; GBF, global biventricular failure; LGE, late gadolinium enhancement; EGE, early gadolinium enhancement AF, atrial fibrillation; PAP, pulmonary artery pressure; LVSF, left ventricular systolic function; RVSF, right ventricular systolic function; RHF, right heart failure; CHB, complete heart block; MI, myocardial infarction; MAB, multiple apical thrombi; CAB, complete atrioventricular block(a* = 9 (Norwood et al, 2017; Ganatra and Neilan, 2018; Katsume et al, 2018; Monge et al, 2018; Thibault et al, 2018; Agrawal et al, 2019; Charles et al, 2019; Sakai et al, 2019; Sharma et al, 2019). (b* = 7) (Ederhy et al, 2018; Frigeri et al, 2018; Matson et al, 2018; Agrawal et al, 2019; Charles et al, 2019; Fazel and Jedlowski, 2019; Khoury et al, 2019). (c* = 8) (Johnson et al, 2016a; Arangalage et al, 2017; Chen et al, 2018; Martin Huertas et al, 2019; Salem et al, 2019).…”
Section: The Diagnosis Of Immune Checkpoint Inhibitor-associated Cardmentioning
confidence: 99%
“…(a* = 9 (Norwood et al, 2017; Ganatra and Neilan, 2018; Katsume et al, 2018; Monge et al, 2018; Thibault et al, 2018; Agrawal et al, 2019; Charles et al, 2019; Sakai et al, 2019; Sharma et al, 2019).…”
Section: The Diagnosis Of Immune Checkpoint Inhibitor-associated Cardmentioning
confidence: 99%
See 1 more Smart Citation
“…In case reports extracted from literature (Singh et al, 2016;Boekstegers et al, 2017;Braun et al, 2017;Haverkos et al, 2017;Klobuch et al, 2017;Onizuka et al, 2017;Herbaux et al, 2018;Charles et al, 2019;Kim et al, 2019;Minson et al, 2019), when mentioned, ICI was indicated for disease relapse after allo-HSCT in 17/22, 77.3%. In one case of nivolumab-associated GVHD, biopsy showed PD-L1 expression in skin, liver and muscular tissues (those with active GVHD) (Charles et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of myocarditis is ∼0.06% in nivolumab treatment and relatively higher with combination blockade (0.27%) of ipilimumab (Johnson et al, 2016). To our knowledge, fatal simultaneous multiorgan failure has rarely been reported (Charles et al, 2019;Hyun et al, 2019). Here, we reported a case where cardiac pacemaker and high-dose steroids successfully controlled the simultaneous fulminant myocarditis, myasthenia gravis crisis, and hepatic dysfunction, and delayed pneumonitis in a patient with lung LCNEC caused by pembrolizumab plus chemotherapy.…”
Section: Introductionmentioning
confidence: 86%